Psychological distress and its predictors among hospital admitted COVID-19 patients in India - R. Pillai, Renjith; Ghosh, Abhishek; Shrivasthava, Sumit; Muralidharan, Sanuj; Kumar, Krishan; S. Kumar, Saranya (International Journal Of Community Medicine And Public Health, 2023)
Background: Limited evidence is available on the psychological distress among patients hospitalized with COVID -19. We assessed the incidence of psychological distress, posttraumatic symptoms and substance use among patients hospitalized with COVID-19; and perceived stress, coping, and social support experienced by distressed and non-distressed patients and the predictors of psychological distress. Methods: Ours was a hospital-based cross-sectional study, conducted in a Union Territory of India. Patients were assessed (August – September, 2020) at the time of admission (within two days) with standardized instruments (N=250). Results: More than 19 percent of respondents had experienced significant psychological distress (probable cases) and nearly 9% reported post-traumatic stress symptoms. The cases and non-cases differ in terms of active coping (5.51±0.87 versus 5.06±1.06; t=3.10, p<0.01), emotional support (5.21±0.87 versus 4.86±0.79; t=2.57, p<0.01), behavioural disengagement (5.18±0.92 versus 4.55±1.15; t=3.56, p<0.001), venting (5.42±0.96 versus 4.80±1.24; t=3.30, p<0.01), acceptance (5.75±1.24 versus 5.29±1.50; t=2.23, p<0.05), religion (5.43±1.41 versus 6.06±1.46; t=-2.76, p<0.01) and self-blame (5.65±1.00 versus 4.82±1.39; t=3.95, p<0.001). Symptoms of post-traumatic stress (OR: 2.058; 95% CI: 1.49-2.84) was the only significant predictor of the psychological distress. Conclusions: Nearly one in five hospitalized patients with COVID-19 experience psychological distress. Screening and treatment for trauma and psychological distress should be an integral component of care for patients with COVID-19.